2021
DOI: 10.1007/s40670-021-01430-8
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Medical Education: Its Nature and Nurture — a Qualitative Study of the Views of Students and Tutors

Abstract: Context Medical education is committed to teaching patient centred communication and empathy. However, quantitative research suggests empathy scores tend to decline as students progress through medical school. In qualitative terms, there is a need to better understand how students and tutors view the practice and teaching of clinical empathy and the phenomenon of empathic erosion. Methods Working within a constructivist paradigm, researchers thematically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Our findings thus point to a fundamental contradiction in medical education: that students, through the introduction of the medical humanities components in the preclinical years are encouraged to become empathic, compassionate and person-centred physicians but that these values are overshadowed by values such as emotional insulation and objectivity. These findings confirm arguments within existing research [ 39 , 46 ], namely, that communication of values on a subtle and hidden level influence students’ valuation of humanistic approaches to medicine, giving rise to personal value conflicts and dilemmas in students who find it difficult to navigate in an educational terrain representing the formal and the informal (hidden) curriculum.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings thus point to a fundamental contradiction in medical education: that students, through the introduction of the medical humanities components in the preclinical years are encouraged to become empathic, compassionate and person-centred physicians but that these values are overshadowed by values such as emotional insulation and objectivity. These findings confirm arguments within existing research [ 39 , 46 ], namely, that communication of values on a subtle and hidden level influence students’ valuation of humanistic approaches to medicine, giving rise to personal value conflicts and dilemmas in students who find it difficult to navigate in an educational terrain representing the formal and the informal (hidden) curriculum.…”
Section: Discussionsupporting
confidence: 88%
“…Contextual factors such as ‘hidden curriculum’ is also widely known to take place outside the clinical setting, which fosters competitiveness and performance above collaboration 89. Hidden curriculums erode professional behaviour and decreases compassion, empathy and increases cynicism and burn-out among healthcare professionals 89–91. Essentially, authors can hypothesise the reason (mechanism) to why this review’s findings suggests using emotional intelligence components, such as awareness (TP4), to structure the learning process 59…”
Section: Discussionmentioning
confidence: 98%
“…89 Hidden curriculums erode professional behaviour and decreases compassion, empathy and increases cynicism and burn-out among healthcare professionals. [89][90][91] Essentially, authors can hypothesise the reason (mechanism) to why this review's findings suggests using emotional intelligence components, such as awareness (TP4), to structure the learning process. 59…”
Section: Learning Processmentioning
confidence: 99%
“…What kind of student should be selected for medical education is an important question which Western countries are trying to grapple with since the 1980s. [6][7][8] Unfortunately, it was also found that innate empathy to fellowmen which every human being has is reduced as the students' progress through their study curriculum; pointing to serious defects in the undergraduate teaching methods. [8] Most of the entrance examination looks for clear-cut answer in the form of "yes" or "no, " but in the real life, the medical practitioners eventually are going to practice in social milieu with many imponderables and empathy.…”
Section: Selection Of Students For Undergraduate Curriculummentioning
confidence: 99%
“…[6][7][8] Unfortunately, it was also found that innate empathy to fellowmen which every human being has is reduced as the students' progress through their study curriculum; pointing to serious defects in the undergraduate teaching methods. [8] Most of the entrance examination looks for clear-cut answer in the form of "yes" or "no, " but in the real life, the medical practitioners eventually are going to practice in social milieu with many imponderables and empathy. None of the examinations really tests this faculty anywhere in the world.…”
Section: Selection Of Students For Undergraduate Curriculummentioning
confidence: 99%